Allicin-inspired thiolated fluoroquinolones as antibacterials against ESKAPE pathogens. Issue 22 (15th November 2016) - Sheppard, Jordan G.; Long, Timothy E.
Graphical abstract: Abstract: Thiolated fluoroquinolones were synthesized from ciprofloxacin and evaluated for antimicrobial activity against a panel of pathogenic bacteria. Gram-positive species including methicillin-resistant Staphylococcus aureus (MRSA) exhibited the highest level of increased sensitivity toward ciprofloxacin bound with a N -propylthio substituent. Evidence was found that the antibiotics form disulfides with low molecular weight thiols in bacteria and potentiate generation of cytosolic reactive oxygen species (ROS). In final analysis, the enhanced anti-MRSA activity of thiolated fluoroquinolones was attributed to increased cell permeability and reaction with cytosolic thiols that yields an inactive disulfide metabolite and the parent drug ciprofloxacin as an inhibitor of DNA synthesis.